Privately financed highways and the challenge to sustainable transportation in Lima - Stiglich, Matteo (AESOP, 2016)
During the last few years, several Latin American cities have implemented sustainable transport policies, including the construction of Bus Rapid Transit systems and the promotion of bicycle use. Furthermore, some of these policies have traveled both between Latin American cities and elsewhere, often being promoted by local governments (Wood 2014; Hidalgo and Gutiérrez 2013). The trend in the expansion of sustainable transport policies, however, should be problematized. In this presentation, I will do so by looking at the contradictions found in a city that has been understudied in the transportation planning field recently. In 2010, Lima's 26km-long Bus Rapid Transit (BRT) line opened at a cost of US$300 million. Initially, the idea was to build a network that would eventually replace a chaotic transit system, providing instead high-quality public transportation. However, just a year later, these plans were scrapped. Instead of expanding the BRT system, the municipal government decided to carry out a regulatory reform that required very little infrastructure spending. The construction of the BRT line had been funded largely using the revenue stream that came form the municipal owned toll roads. Starting in 2012, those revenues were redirected toward the improvement and expansion of the highway network. Furthermore, this expansion will be financed privately by corporations that will take control of the existing toll roads and are raising a total of US$2bn.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south